PET-Based Percutaneous Needle Biopsy - El-Haddad, Ghassan (PET clinics, 2016)
PET can be used to guide percutaneous needle biopsy to the most metabolic lesion, improving diagnostic yield. PET biopsy guidance can be performed using visual or software coregistration, electromagnetic needle tracking, cone-beam computed tomography (CT), and intraprocedural PET/CT guidance. PET/CT-guided biopsies allow the sampling of lesions that may not be clearly visible on anatomic imaging, or of lesions that are morphologically normal. PET can identify suspicious locations within complex tumors that are most likely to contain important diagnostic and prognostic information.